ADVANCED FOREIGN EXPERIENCE IN THE DEVELOPMENT OF INVESTMENT ACTIVITIES OF COMMERCIAL BANKS - Malikova Gulhayo Turdali qizi (European Science Publishing, 2024)
This article analyzes the investment activity of commercial banks, advanced foreign experience in the development of investment activity of commercial banks. Based on the literature analysis and the results of the conducted research, scientific and practical proposals for further development of the field are given.
Keywords: Investment, indicators, commercial banks, centeral bank.